1998
DOI: 10.1111/1467-9248.00161
|View full text |Cite
|
Sign up to set email alerts
|

Funding the Welfare State: Globalization and the Taxation of Business in Advanced Market Economies

Abstract: Theorists assert that international capital mobility creates substantial pressure for all democratically elected governments to decrease tax burdens on business. I explicate and critique the general version of this theory and oer an alternative view. Empirically, I explore whether or not the globalization of capital markets has resulted in decreases in business social security, payroll, and pro®t taxes. I also investigate whether or not capital mobility has intensi®ed government responsiveness to domestic inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
169
0
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(181 citation statements)
references
References 2 publications
3
169
0
8
Order By: Relevance
“…These explanations state that, in the 1970s, policymakers had become increasingly dissatisfi ed with taxation systems that intervened in the structure of savings and investments and thus, in the 1980s, started to move toward more "market-conforming" systems by lowering statutory rates and broadening tax bases (Swank 1998;Steinmo 2003;Stewart/Webb 2006). These explanations are no challenge to the tax competition hypothesis because, even if "market conformity" is the goal, there are good reasons to maintain relatively high company tax rates on above-normal profi ts.…”
Section: The Indirect Effects Of Company Tax Competition: Theorymentioning
confidence: 99%
“…These explanations state that, in the 1970s, policymakers had become increasingly dissatisfi ed with taxation systems that intervened in the structure of savings and investments and thus, in the 1980s, started to move toward more "market-conforming" systems by lowering statutory rates and broadening tax bases (Swank 1998;Steinmo 2003;Stewart/Webb 2006). These explanations are no challenge to the tax competition hypothesis because, even if "market conformity" is the goal, there are good reasons to maintain relatively high company tax rates on above-normal profi ts.…”
Section: The Indirect Effects Of Company Tax Competition: Theorymentioning
confidence: 99%
“…One good example of this possibility is globalization. The important role of union power and top marginal tax on the top 1% revealed in this article draws our attention to the literature on the impact of globalization on union density and taxation policy (Western 1998;Swank 1998;Brady, Beckfield, and Zhao 2007;Hays 2003;Scruggs and Lange 2002). To the extent that globalization erodes union power (for example through deindustrialization) and increases the pressure towards lowering top marginal taxes, globalization may have created a favorable "context" for the abovenoted self-reinforcing cycle of income, wealth, and power concentration in politics.…”
Section: Resultsmentioning
confidence: 92%
“…Die bisherigen Auswirkungen des Steuerwettbewerbs zeigen sich mithin zum Teil eher in umstrittenen Veränderungen der Struktur der Einkommensbesteuerung als in umfangreichen Einnahmeverlusten. Recent studies in political science have found that despite increased economic internationalization, neither capital (income) tax revenues, nor total tax revenue nor public expenditures in advanced OECD countries have shown an average downward trend, and that higher degrees of global market integration have not systematically translated into lower capital tax revenues, total tax revenues, or public expenditures (Garrett 1998a;1998b;1998c;Quinn 1997;Swank 1997). These results are striking.…”
Section: Zusammenfassungmentioning
confidence: 98%